IDENTIFIKASI DAN KUALITAS SERAT LIMA JENIS KAYU ANDALAN SETEMPAT ASAL JAWA BARAT DAN BANTEN - Sri Rulliaty (BRIN Publishing, 2014)
General characteristics, anatomical properties and fiber quality of five locally potential wood species from West Java and Banten, have been examined for wood identification purposes. The main characteristics of those five wood species based on IAWA List of Microscopic Features for Hardwood Identifications were described in the following : Pisonia umbelliflora (Forst) Seem (ki cau) has heartwood dry straw colored to yellow pale in distinctly demarcated from its sapwood, rather hard, grain interlocked, vessels clustered, parenchyma vasicentric and in narrow band or lines up to three cells wide, rays exclusively uniseriate, fibres with simple to minutely bordered pits, crystals raphides type in procumbent ray cells present; Litsea monopetala Pers. (huru manuk) has heartwood white cream-colored indistinctly demarcated from sapwood, rather hard, grain straight, vessels exclusively solitary, parenchyma vasicentric, all ray cells procumbent and has oil cells associated with axial parenchyma; Buchanania arborescens Blume (ki renggas) heartwood white pinkish clearly differentiated from sapwood, hard, patterned on radial section, grain interlocked, vessels in radial multiples, parenchyma diffuse, rays larger commonly up to 6 seriate, prismatic crystals present in upright ray cells and chambered axial parenchyma cells; Crypteronia paniculata Blume (ki banen) heartwood brownish to yellow slightly deep brown, grain straight slightly interlocked sometime twisted, vessel diffuse, parenchyma diffuse in aggregate, rays 1-3 seriate, fibers thin to thick, prismatic crystal in procumbent cell; Ficus ampelas Burm. f. (ki hampelas) has heartwood white creamy pinkish colored clearly differentiated from the sapwood, grain straight slightly interlocked, vessel exclusively solitary, tyloses common, parenchyma banded 2-8 cells wide, rays larger commonly not 9 to 5 seriate, sheath cells present, fibers with simple to minutely bordered pits. Fibre quality of those five woods could be classified into quality class I. Further study regarding their processing for pulp and paper is preferable.